Association Between Serum Vitamin D Levels and Parkinson's Disease: A Systematic Review and Meta-Analysis - Luo, Xiaoyue; Ou, Ruwei; Dutta, Rajib; Tian, Yuan; Xiong, Hai; Shang, Huifang (Frontiers in Neurology, 2018)
Background: Vitamin D is an important secosteroid which is involved the development and regulation of brain activity. Several studies have focused on exploring the relationship between serum vitamin D levels and Parkinson’s disease (PD), but the conclusion remains ambiguous. Methods: We searched observational studies that explored the association between serum vitamin D levels and PD based on PubMed, EMBASE and Cochrane library from inception through to December 2017. The quality of included studies was evaluated by using Newcastle-Ottawa Scale（NOS）. Statistical analysis of this meta-analysis was performed by Stata version 12.0 and R software. Results: Twenty-one studies with a total of 3052 PD patients and 3536 controls were included. Compared with controls, PD patients had lower serum vitamin D levels (WMD -5.21, 95%CI -6.48, -3.94), especially in higher latitude regions (WMD -5.53, 95%CI -7.49, -3.57). Assay methods contributed significantly to high heterogeneity. Furthermore, PD patients with deficient vitamin D levels had advanced risk (OR 2.08, 95%CI 1.35, 3.19) than those patients with insufficient ones (OR=1.73, 95%CI 1.48, 2.03). In addition, serum vitamin D levels were also related to the severity of PD (WMD-6.31, 95%CI -9.13, -3.50) and the summary correlation coefficient showed strongly negative correlation (r=-0.61, 95%CI -0.76, -0.39). Moreover, the pooled correlation coefficient revealed that serum vitamin D levels were also negatively correlated to the Unified Parkinson’s Disease Rating Scale III (UPDRS III) (r=-0.36, 95%CI -0.53, -0.16), but did not correlate with the duration of PD (P=0.37) and age of patients (P=0.49). Conclusion: Serum vitamin D levels are inversely associated with the risk and severity of PD. Our results provided an updated evidence of association between low vitamin D levels and PD and prompt the adjunctive therapeutic decisions about vitamin D replacement in PD.